The past, present and future of Euro area monetary-fiscal interactions - Karl Whelan (University College Dublin, UCD School of Economics, 2022)
The EU's Treaties were designed to limit the interaction between fiscal and monetary policies. However, over the last decade, the introduction of the ECB's Outright Monetary Transactions (OMT) programme and its sovereign bond purchase programmes have created some strong linkages between monetary and fiscal policies in the Eurosystem. The ECB's monetary policies have improved fiscal debt sustainability and reduced the probability of sovereign default. However, there may need to be limits to the ECB's purchases of sovereign bonds. This paper discusses the interactions between fiscal and monetary policies in the euro area and describes how the arguments raised by the European Court of Justice in the Weiss and Gauweiler cases suggest there may be hard limits on the size of the Eurosystem's sovereign bond holdings. These limits may undermine the positive impact of the OMT announcement and force the ECB into some difficult choices in the coming years.
Keywords: 330